Ceftazidime-Induced Overexpression of MexJK-OprM Confers Resistance to Ceftolozane/Tazobactam in an Isolate of Pseudomonas aeruginosa - Sato T; Tamura M; Kaimori K; Okumura F; Ikejima S; Nakai H; Kawamura M; Fujimura S (Infection and Drug Resistance)
Takumi Sato,1 Mai Tamura,2,3 Kei Kaimori,1 Fumihiko Okumura,4 Shin Ikejima,3 Hajime Nakai,2,3 Masato Kawamura,1 Shigeru Fujimura1 1Division of Clinical Infectious Diseases & Chemotherapy, Graduate School of Pharmaceutical Sciences, Tohoku Medical and Pharmaceutical University, Sendai, Miyagi, Japan; 2Department of Pharmacy, Odate Municipal General Hospital, Odate, Akita, Japan; 3Department of Infection Control, Odate Municipal General Hospital, Odate, Akita, Japan; 4Department of Respiratory Medicine, Odate Municipal General Hospital, Odate, Akita, JapanCorrespondence: Takumi Sato, Division of Clinical Infectious Diseases & Chemotherapy, Graduate School of Pharmaceutical Sciences, Tohoku Medical and Pharmaceutical University, 4-4-1 Aoba-ku, Sendai, Miyagi, 981-8558, Japan, Tel +81-022-727-0176, Fax +81-022-727-0177, Email tsato@tohoku-mpu.ac.jpObjective: The emergence of resistance to ceftolozane/tazobactam (CTLZ/TAZ) in Pseudomonas aeruginosa poses a significant clinical challenge. This study investigates the mechanisms underlying CTLZ/TAZ resistance in a clinical isolate and examines the role of prior antibiotic exposure.Methods: A TAZ/CTLZ-resistant P. aeruginosa strain (Pa-R) was isolated from a patient with a lung abscess after six weeks of antibiotic therapy. Genetic relatedness between Pa-R and a pre-treatment susceptible strain (Pa-S) was assessed using PCR-based open reading frame typing (POT). Carbapenemase genes were detected via multiplex PCR. Sequencing and expression analyses of ampC, ftsI, oprD, and mex family genes were conducted. RNA interference targeting mexJK was performed to validate its role in resistance. In vitro antimicrobial exposure assays were conducted to evaluate resistance acquisition and the impact of prior ceftazidime (CAZ) exposure.Results: Pa-R and Pa-S were genetically identical and lacked carbapenemase genes. No mutations or overexpression of ampC were observed; however, mexJK expression was approximately 30-fold higher in Pa-R. RNA interference using mexJK-specific dsRNA restored CTLZ/TAZ susceptibility, confirming that high MexJK-OprM expression is the mechanism of resistance. In vitro assays demonstrated that CTLZ/TAZ alone did not induce resistance, whereas prior CAZ exposure led to CTLZ/TAZ resistance accompanied by mexJK overexpression.Conclusion: This study demonstrated that overexpression of the MexJK-OprM efflux pump is a key mechanism underlying TAZ/CTLZ resistance. In addition, prior administration of CAZ contributed to the acquisition of resistance, highlighting the need to consider the risk of resistance acquisition when switching antibiotics. In such cases, the choice of carbapenems should be considered.Plain Language Summary: Ceftolozane/tazobactam -resistant P. aeruginosa strain was isolated from a patient with a lung abscess after six weeks of antibiotic therapy.Overexpression of the MexJK-OprM efflux pump is a key mechanism underlying ceftolozane/tazobactam resistance.The prior administration of ceftazidime contributed to the acquisition of ceftolozane/tazobactam resistance.Keywords: Pseudomonas aeruginosa, ceftolozane/tazobactam, antimicrobial resistance, efflux pump, MexJK